Metabolic response to desiccation stress in strains of green algal photobionts (Trebouxia) from two Antarctic lichens of southern habitats. Issue 6 (1st November 2016) - Sadowsky, Andres; Mettler-Altmann, Tabea; Ott, Sieglinde
Abstract: Desiccation tolerance is a feature of most lichens. These symbiotic associations of a fungal partner (mycobiont) and a photosynthetic partner (photobiont) experience severe desiccation on a regular basis. Many lichen species colonise extreme habitats, such as the cold deserts of Antarctica. Although the stress physiology of lichens has been studied extensively, little is known about the photobionts' physiological potential. To assess the contribution of photobionts to lichen success in Antarctic terrestrial environments, the photosynthetic partners of Umbilicaria decussata (Umbilicariaceae, lichenised ascomycetes) and Usnea lambii (Parmeliaceae, lichenised ascomycetes) from extreme habitats in southern Antarctica were isolated. Significant differences regarding stress tolerance of the two green algae had been shown previously despite their close phylogenetic relationship. A deeper understanding and explanation of these differences were obtained by examination of the metabolite profiles and dynamics, especially the role of sugars, polyols and amino acids. High concentrations of ribitol and sucrose, among other metabolites, characterised the photobiont of Usnea lambii 's mainly constitutive strategy of desiccation tolerance. A high degree of specialisation to dry environments can be assumed for this photobiont.